Analisis Makna pada Video Musik Kamu & Kenangan (Semiotika Ferdinand de Saussure) - Auralia, Anisa Safitri; Rifani Khoirunnisa (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2023)
The music video of Kamu & Kenangan was created by famous musician Melly Goeslaw and performed by young actress Maudy Ayunda. The lyrics of this song tell about regret, loneliness, and a deep sense of loss due to being abandoned by someone you love. This song became the original song for the film Habibie & Ainun 3, Pak Habibie tells the story of young Ainun's struggle in studying for his children and grandchildren. Maudy Ayunda in the music video represents all the emotions Mr. Habibie felt for the loss of Mrs. Ainun. In this study, there is an urgency for the object under study in the form of representations and meanings in the music video. The purpose of this study is to explain implicit and explicit emotions. That way, understanding will come about how songs can convey feelings to those who hear and see the expressions given. This study also provides a lesson on positive values such as divinity, sincerity, true love, and can inspire us to continue to strive to be human beings who are devoted to the Owner of Love. The theory used is the theory of semiotics from Ferdinand de Saussure, signifiers in the video are in visual language, cinematic, expression, movement, facial expressions, and song lyrics. While the signified lies in the meaning of the lyrics and the values contained.